2022
DOI: 10.3390/su14159311
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Pro-Environmental Behaviour amongst Citizens in African Countries: A Cross-National Study amongst Six African Countries

Abstract: The role of pro-environmental behaviour in environmental care and mitigation of environmental problems is widely recognised. However, most studies on pro-environmental behaviour have focused on populations living in Western and high-income countries and only a few studies are available in developing countries. In this paper, we explored and compared the determinants of pro-environmental behaviour of citizens in six African countries, namely Algeria, Egypt, Ghana, Nigeria, South Africa and Zimbabwe. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Factors such as gender, employment status, sector of employment and social class were found to be positively correlated with responsible environmental behavior in certain countries, in agreement with the results stemming from previous studies. On the other hand, for the data pertaining to South Africa, education, income and environmental organization membership were negatively related to responsible environmental behavior (Ifegbesan et al, 2022). Other results have shown that South African peoples revealed significant differences in their responsible environmental behavior according to education.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as gender, employment status, sector of employment and social class were found to be positively correlated with responsible environmental behavior in certain countries, in agreement with the results stemming from previous studies. On the other hand, for the data pertaining to South Africa, education, income and environmental organization membership were negatively related to responsible environmental behavior (Ifegbesan et al, 2022). Other results have shown that South African peoples revealed significant differences in their responsible environmental behavior according to education.…”
Section: Introductionmentioning
confidence: 99%
“…Africa seems to be the greatest casualty of climate change and has been classified as the world's most vulnerable region to the impacts of climate change due to the continent's poor adaptive capacity (Awojobi, 2017). The devastating impacts of climate change on the continent have significantly affected economic sectors, natural resources, ecosystems, livelihoods, and human health, primarily due to human maladaptive behaviour (Ifegbesan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%